Teachers’ Experiences and Instructional Practices in Utilizing Information and Communication Technology (ICT) for Mathematics Teaching - RAMOS, SUNSHINE; AMIN, JESSIE (Studies in Technology and Education, 2026)
The integration of Information and Communication Technology (ICT) in Mathematics education has become increasingly significant in enhancing learner engagement, conceptual understanding, and instructional delivery in elementary schools. In the Philippine educational context, teachers are encouraged to utilize digital technologies and innovative teaching approaches to support learner-centered instruction and improve learning outcomes in Mathematics. This qualitative phenomenological study explored the experiences and instructional practices of public elementary school teachers in utilizing ICT for Mathematics teaching in Diffun District I, Division of Quirino. Specifically, the study examined teachers’ instructional strategies, classroom experiences, challenges encountered, coping mechanisms, and professional perspectives regarding ICT integration in Mathematics instruction. Twelve public elementary school teachers were purposively selected as participants. Data were gathered through semi-structured interviews, classroom observations, and document analysis of lesson plans and digital instructional materials. Braun and Clarke’s thematic analysis framework was employed in analyzing the collected data. Findings revealed that teachers utilized ICT to enhance learner engagement, simplify mathematical concepts, and promote interactive classroom participation through multimedia presentations, educational applications, online resources, and digital activities. However, participants also experienced challenges related to insufficient technological resources, unstable internet connectivity, limited ICT infrastructure, inadequate technical support, and lack of advanced ICT training. Despite these challenges, teachers demonstrated adaptability, innovation, and professional commitment by maximizing available resources, engaging in collaborative learning, and continuously improving their technological competencies. The study concluded that effective ICT integration in Mathematics education requires sustained institutional support, continuous teacher training programs, strengthened technological infrastructure, and accessible digital learning resources. The findings contribute to the growing discourse on ICT integration, Mathematics pedagogy, and educational innovation in Philippine elementary education.